2015
DOI: 10.1021/jf505015y
|View full text |Cite
|
Sign up to set email alerts
|

Insect-Protected Event DAS-81419-2 Soybean (Glycine maxL.) Grown in the United States and Brazil Is Compositionally Equivalent to Nontransgenic Soybean

Abstract: The transgenic soybean event DAS-81419-2 contains genes that encode the Cry1F, Cry1Ac, and PAT proteins. Cry1F and Cry1Ac provide protection against key lepidopteran insect pests, while PAT confers tolerance to the herbicide glufosinate. To satisfy regulatory requirements for the safety evaluation of transgenic crops, studies were conducted in the United States and Brazil to evaluate the nutrient and antinutrient composition of event DAS-81419-2 soybean. On the basis of the results of these studies, event DAS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 108 publications
(233 reference statements)
3
14
0
Order By: Relevance
“…On the other hand, Herman et al (2011) Recent studies have examined other issues, such as the ecological interactions of Roundup Ready 2 YieldR-soybean (MON 89788), without founding effects of the genetic modification that could result in increased pest potential or adverse environmental impact of that transgenic soybean (Horak et al, 2015). In turn, Fast et al (2015) determined the nutrient and antinutrient composition of event DA-81419-2 soybean, which was equivalent to non-transgenic soybean.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…On the other hand, Herman et al (2011) Recent studies have examined other issues, such as the ecological interactions of Roundup Ready 2 YieldR-soybean (MON 89788), without founding effects of the genetic modification that could result in increased pest potential or adverse environmental impact of that transgenic soybean (Horak et al, 2015). In turn, Fast et al (2015) determined the nutrient and antinutrient composition of event DA-81419-2 soybean, which was equivalent to non-transgenic soybean.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…1 However, over 100 scientific studies on GE-crop composition have been conducted over the past 25 years and have clearly demonstrated that transgenesis is less likely to cause unexpected changes in crop composition compared with traditional breeding methods. 2,3 Therefore, transgenesis has been shown to not create novel or increased risks compared with traditional breeding. 2,4,5 Despite this wealth of evidence, the complexity and cost of crop-composition studies to support GE-crop approvals have increased tremendously over time, and some scientists are still suggesting even further complexity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, several research teams reported no alteration in the total daidzein, total genistein. and total glycitein in soybeans being genetically modified for herbicide tolerance, insect resistance, and modified fatty acid profile (Padgette et al, 1996;Taylor et al, 1999;Mc Cann et al, 2005;Lundry et al, 2008;Berman et al, 2009Berman et al, , 2010Zhou et al, 2011a;Lepping et al, 2013;Fast et al, 2015).…”
Section: Factors Influencing Isoflavone Contentmentioning
confidence: 99%